Motivating Factors in Foreign Volunteering: Tibor Péchy’s Enlistment in the Anglo-Boer War - Szabó-Zsoldos, Gábor (Acta Neerlandica, 2023)
Twelve Hungarian volunteers have been identified so far among the 2,500 pro-Boerforeign volunteers who were ready to sacrifice their lives in the war between the Boerrepublics and the British Empire (1899–1902). The overwhelming majority of thesevolunteers travelled to South Africa to join the commandos of the Boers following theescalation of the conflict. Tibor Péchy was one of the Hungarian combatants, but incontrast with the other Hungarian volunteers, he had been living in South Africa since1896. This makes him a special Hungarian participant of the Anglo-Boer War. The presentpaper analyses the motivating factors behind Péchy’s enlistment with the Boers.